Sepsis - strategy of management - Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2009)
Evidence-based recommendations should be considered in the management of sepsis. Resuscitation and therapeutical elements are basic steps in clinical procedures applied in patients with acute sepsis. Monitoring of live parameters during therapy is important to reach the clinical stabilization of patient. One of the most important steps of management in sepsis is to obtain the proper material for microbiological evaluation before antibiotic therapy will be applied. Next, when the clinical control of circulatory and respiratory functions will be sufficient the recombinant human activated protein C (rhAPC) may be considered for the treatment of severe sepsis in patients with a high risk of death.